Immunologic Monitoring of T-Lymphocyte Subsets and HLA-DR-Positive Monocytes in Kidney Transplant Recipients: A Prospective, Observational Cohort Study. Issue 44 (November 2015) - Cho, Jang-Hee; Yoon, Young-Deuk; Jang, Hye Min; Kwon, Eugene; Jung, Hee-Yeon; Choi, Ji-Young; Park, Sun-Hee; Kim, Yong-Lim; Kim, Hyung-Kee; Huh, Seung; Won, Dong-Il; Kim, Chan-Duck
Abstract : Abstract: The clinical significance of circulating T-lymphocyte subsets and human leukocyte antigen (HLA)-DR-positive monocytes in the peripheral blood of kidney transplant recipients (KTRs) remains unclear. We examined the efficacy of enumerating these cells for the immunologic monitoring of KTRs. Blood samples were obtained before transplantation, 2 weeks after transplantation and at diagnosis, and 2 weeks after treating biopsy-proven acute cellular rejection and cytomegalovirus (CMV) infection. Serial flow cytometric analysis was performed using peripheral blood obtained from 123 patients to identify the frequencies of HLA-DR +, CD3 +, CD4 +, CD8 +, and CD25 + T-lymphocytes and HLA-DR-positive monocytes. Frequencies of CD4 + CD25 + /CD4 + T cells, CD8 + CD25 + /CD8 + T cells, and HLA-DR-positive monocytes were significantly lower at 2 weeks after transplantation than before transplantation (all P  < 0.001). This decrease was not correlated with clinical parameters. The frequency of CD4 + CD25 + /CD4 + T cells was significantly higher in KTRs with acute rejection than in KTRs at 2 weeks after transplantation (9.10% [range 4.30–25.6%] vs 5.10% [range 0.10–33.3%]; P  = 0.024). However, no significant differences were observed between stable KTRs and KTRs with CMV infection. Analysis of the receiver operating characteristic curve adjusted by covariates showed that acute rejection could be predicted with 75.0% sensitivity and 68.4% specificity by setting the cutoff value of CD4 + CD25 + /CD4 + T cell frequency as 5.8%. Circulating T-lymphocyte and monocyte subsets showed significant and consistent changes in their frequencies after immunosuppression. Of the various immune cells examined, circulating levels of CD4 + CD25 + T cells might be a useful noninvasive immunologic indicator for detecting acute rejection.